Moody’s Catholic Ratings: Institutional Communication of the Church for Issuing Religious Bonds - Mendoza, Cristian (Roczniki Nauk Społecznych, 2024)
The issuance of religious bonds by some American Catholic dioceses is a model of ecclesiastical financing that works thanks to the institutional communication of the Church in the economic field. This procedure, by which important resources are obtained in case of emergency, requires from those responsible for the administration of temporal goods a creative and clear institutional communication. Credit rating agencies present the financial situation of the diocese, especially to obtain new investors. Diocesan administrators usually turn to the faithful when they need more resources, but this system of issuing religious debt in the stock market represents a novel effort that can be imitated by other ecclesiastical entities.